2015
DOI: 10.1371/journal.pone.0122649
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Squalene Epoxidase Genes from Botryococcus braunii, Race B

Abstract: The B race of the green microalga Botryococcus braunii produces triterpene hydrocarbons, botryococcenes and methylsqualenes that can be processed into jet fuels with high heating values. In this alga, squalene is also converted into membrane sterols after 2,3-epoxidation. In the present study, cDNA clones of two distinct squalene epoxidases (BbSQE-I and -II) were isolated. Predicted amino acid sequences encoded on these genes are 45% identical with each other. Introduction of BbSQE-I or -II into Saccharomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this study, squalene was found to be 2.42%. Squalene can also be used as biofuel feedstock through methylation that can also be converted to sterol membrane through epoxidation process (Uchida et al, 2015). The most common hydrocarbon found in B320 is pentacosane (8.61%) that is a saturated aliphatic hydrocarbon generally found in beeswax.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, squalene was found to be 2.42%. Squalene can also be used as biofuel feedstock through methylation that can also be converted to sterol membrane through epoxidation process (Uchida et al, 2015). The most common hydrocarbon found in B320 is pentacosane (8.61%) that is a saturated aliphatic hydrocarbon generally found in beeswax.…”
Section: Resultsmentioning
confidence: 99%
“…Squalene (27) is metabolized into squalene 2,3-epoxide (28) in higher plants (Uchida et al 2007b), which is subsequently converted into membrane sterols. While two squalene 2,3-epoxidase have been found in B. braunii (Uchida et al 2015), some squalene derivatives appear to be epoxidized at the 10,11 positions. Tetramethylsqualene 10,11-epoxide (34) (Delahais and Metzger 1997) might be covalently conjugated with carotenoids to form botryoxanthin (Okada et al 1996) or braunixanthin (Okada et al 1997), and these compounds might be excreted to the extracellular matrix (right panel in Fig.…”
Section: Biosyntheses Of Isoprenoids and Triterpenesmentioning
confidence: 94%
“…Three cyclic botryococcene C 33 molecules and a trimethylsqualene isomer were recently found [44]. Also, two squalene epoxidase (BbSQE-I and -II) enzymes converting squalene into membrane sterols were identified [45]. Data of the B. braunii race B nuclear genome will allow the search for possible regulatory routes of this singular metabolism [46].…”
Section: Lycopadiene Biosynthetic Pathway (A) Reduction Of Ggpp To Pmentioning
confidence: 99%